PENGEMBANGAN BAHAN AJAR MATEMATIKA VOKASI DIGITAL BERBASIS STEM DI SMK PADA MATERI TRIGONOMETRI - I Komang Sukendra; I Made Surat; I Made Darmada (Widyadari : Jurnal Pendidikan, 2022)
Vocational education is higher education that supports the mastery of certain applied skills and mathematics is a universal language for presenting ideas or knowledge in a formal and precise manner so that it does not allow for multiple interpretations. This study aims to determine the quality of the development of STEM-based digital vocational mathematics teaching materials on Trigonometry materials in SMK. The research and development procedure uses the Plomp model which includes five stages, namely initial investigation, design, realization/construction, as well as testing, evaluation and revision and implementation. Sources of data in this study are validators, mathematics teachers and students of SMK Negeri 5 Denpasar. The data collection technique used a validation questionnaire for the validation test, a practicality questionnaire for the practicality test and a test for testing the effectiveness of digital vocational mathematics teaching materials. The results of the initial validity test were declared valid with a value of validity on the content aspect of 0.79, the validity of the presentation aspect of 0.90; language validity 0.93; and media validity 0.94. The results of the second stage of the validity test were declared valid, with a validity value of 0.91. The results of the practicality test on students obtained results of 80.5 and for teachers of 79.5 including the practical category, and the results obtained by students in the evaluation had an average of 84.15. So STEM-based digital vocational mathematics teaching materials are effective for use in learning in SMK.